Health awareness campaign @ Eristana / Norkasihan Ibrahim - Ibrahim, Norkasihan (Faculty of Pharmacy, 2024)
The Faculty of Pharmacy , UiTM took part in the Karnival Perpaduan Eristana event on February 24th, 2024, which was hosted in Rumah Bandar Eristana .